Myeloid-derived suppressor cell-derived osteoclasts with bone resorption capacity in the joints of arthritic SKG mice - Fujikawa, Yoshikazu; Sendo, Sho; del Peral Fanjul, Alfonso; Yamada, Hirotaka; Uto, Kenichi; Yamamoto, Yuzuru; Nagamoto, Takumi; Morinobu, Akio; Saegusa, Jun (Frontiers in Immunology, 2024)
Background. Myeloid-derived suppressor cells (MDSCs) are heterogeneous immature myeloid cells with immunosuppressive functions. It is known that MDSCs are expanded at inflammatory sites after migrating from bone marrow (BM) or spleen (Sp). In chronic inflammatory diseases such as rheumatoid arthritis (RA), previous reports indicate that MDSCs are increased in BM and Sp, but detailed analysis of MDSCs in inflamed joints is very limited.Objective. The purpose of this study is to characterize the MDSCs in the joints of mice with autoimmune arthritis.Methods. We sorted CD11b + Gr1 + cells from joints (Jo), bone marrow (BM) and spleen (Sp) of PAGE ¥* Arabic ¥* SKG mice with zymosan (Zym)-induced arthritis and investigated differentially expressed genes (DEGs) by microarray analysis. Based on the identified DEGs, we assessed the suppressive function of CD11b + Gr1 + cells from each organ and their ability to differentiate into osteoclasts.Results. We identified MDSCs as CD11b + Gr1 + cells by flow cytometry and morphological analysis. Microarray analysis revealed that Jo-CD11b + Gr1 + cells had different characteristics compared with BM-CD11b + Gr1 + cells or Sp-CD11b + Gr1 + cells. Microarray and qPCR analysis showed that Jo-CD11b + Gr1 + cells strongly expressed immunosuppressive DEGs (Pdl1, Arg1, Egr2and Egr3). Jo-CD11b + Gr1 + cells significantly suppressed CD4 + T cell proliferation and differentiation in vitro, which confirmed Jo-CD11b + Gr1 + cells as MDSCs. Microarray analysis also revealed that Jo-MDSCs strongly expressed DEGs of the NF-κB non-canonical pathway (Nfkb2 and Relb), which is relevant for osteoclast differentiation. In fact, Jo-MDSCs differentiated into osteoclasts in vitro and they had bone resorptive function. In addition, intra-articular injection of Jo-MDSCs promoted bone destruction.Jo-MDSCs possess a potential to differentiate into osteoclasts which promote bone resorption in inflamed joints, while they are immunosuppressive in vitro .